2019
DOI: 10.1002/hed.25845
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of dental and craniofacial osseointegrated implantation in head and neck cancer patients

Abstract: Background Treatment of head and neck cancer may result in disfiguring and debilitating anatomical changes. Osseointegrated implants may be used in these patients to facilitate attachment of implant‐retained dentures or cosmetic prostheses. Methods A retrospective audit was performed, reviewing the treatment of patients who received dental or craniofacial osseointegrated implants during treatment of head and neck cancer. Results One hundred sixty implants were inserted in 54 patients with oral, nasal, orbital,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…Whether an implant was loaded or not and the time interval before loading were also found to be influencing the outcome. Adverse to that Moore et al (2019), Woods et al (2019), Jacobsen et al (2014) and Curi et al (2018) found no statistically significant difference in implant placement for the respective factor examined. In those studies, there was neither a difference in implant placement prior to or after radiotherapy (Jacobsen et al, 2014; Moore et al, 2019), nor in the time interval before placement after radiation (Curi et al, 2018).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Whether an implant was loaded or not and the time interval before loading were also found to be influencing the outcome. Adverse to that Moore et al (2019), Woods et al (2019), Jacobsen et al (2014) and Curi et al (2018) found no statistically significant difference in implant placement for the respective factor examined. In those studies, there was neither a difference in implant placement prior to or after radiotherapy (Jacobsen et al, 2014; Moore et al, 2019), nor in the time interval before placement after radiation (Curi et al, 2018).…”
Section: Discussionmentioning
confidence: 89%
“…However, 18 studies investigated in the current literature research were not used for meta‐analysis. Besides the reasoning of too short of a follow‐up (Alberga et al, 2020; Burgess et al, 2017; Ch'ng et al, 2016; Gander et al, 2014; Hessling et al, 2015; Moore et al, 2019; Pompa et al, 2015; Woods et al, 2019), the second reason for exclusion was that the studies only assessed implants placed in irradiated bone, which means they were lacking a non‐irradiated control group (Buurman et al, 2013; Curi et al, 2018; Di Carlo et al, 2019; Nack et al, 2015; Neckel et al, 2020; Papi et al, 2019; Rana et al, 2016; Sandoval et al, 2020). Ettl et al (2020) were reporting implant success using a modified version of the Albrektsson criteria (Albrektsson et al, 1986), and their study was therefore excluded.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Smokers were excluded for participation and soft-tissue augmentations were performed in case of insufficient soft-tissue conditions. Smoking is known to negatively influence endosseous implant survival aside from other variables such as radiation [ 20 ].…”
Section: Introductionmentioning
confidence: 99%